Taxonomic and phylogenetic biases in translocated angiosperm plant species across European countries - Filipa Coutinho Soares; Maud Mouchet; Anne‐Christine Monnet; Nadline Kjelsberg; Alfredo García Fernández; Alexandre Robert; Jean‐Baptiste Mihoub; Bruno Colas; François Sarrazin (Conservation Biology, 2025)
Conservation translocations are a well‐known conservation tool used to reverse the effects of local population extinctions and restore ecosystems. Compared with mammals and birds, plants are underrepresented in translocation programs, and little is known about the potential taxonomic and phylogenetic biases of plant translocation efforts. We aimed to assess how translocated plant species may contribute to the conservation of phylogenetic diversity (PD) among European countries. Focusing on angiosperms across 4 European countries with well‐documented flora and comprehensive sampling of translocated plant species, we determined whether species translocations were related to species conservation status with binomial generalized linear mixed models with threat status as a binary response variable. Then, we evaluated the taxonomic and phylogenetic biases of translocated plant species relative to national floras based on PD and evolutionary distinctiveness (ED). To evaluate PD and ED, we constructed null models to assess the deviation of observed values from those expected under a scenario in which translocated species were randomly sampled from the species pool of national floras in each country. Although most species lacked conservation status assessment, plant translocations mainly targeted species with high extinction risk at national, European, and global scales. Although plant orders with a higher representativeness of translocated species also tended to have a higher representativeness of native species, the probability of species being translocated varied significantly across plant order, suggesting a significant taxonomic bias. Based on null models and considering all countries, PD and mean ED of translocated plants were higher than expected by chance in most countries. These results suggest that although translocation programs were implemented independently across countries, the diversity of translocated plant species is relevant to conserving PD from national to continental scales and restoring evolutionarily distinct species when these species succeed. We argue that PD indicators should be incorporated into translocation planning to restore target species’ evolutionary trajectories and to contribute to conservation of PD.

Current state of plant conservation translocations across Europe: motivations, challenges and outcomes - Sandrine Godefroid; Sam Lacquaye; Andreas Ensslin; Sarah Dalrymple; Thomas Abeli; Hannah Branwood; Inmaculada Ferrando Pardo; P. Pablo Ferrer Gallego; Elke Zippel; Luísa Gouveia; Carlos Alberto Lobo; Francisco Fernandes; et al. (Biodiversity and Conservation, 2025)

Plant Translocations in France: Identifying Gaps between Knowledge, Practice and Perception by Conservation Actors - Margaux Julien; Juliette Ducrettet; Mohamed Diallo; Eric Imbert; Bruno Colas; Bertrand Schatz (Environmental Management, 2024)

Camera trap surveys of A tlantic F orest mammals: A data set for analyses considering imperfect detection (2004–2020) - Ingridi Camboim Franceschi; Rubem Augusto da Paixão Dornas; Isabel Salgueiro Lermen; Artur Vicente Pfeifer Coelho; Ademir Henrique Vilas Boas; Adriano Garcia Chiarello; Adriano Pereira Paglia; Agnis Cristiane de Souza; Alana Rafaela Borsekowsky; Alessandro Rocha; Alex Bager; Alexander Zaidan de Souza; et al. (Ecology, 2024)
Camera traps became the main observational method of a myriad of species over large areas. Data sets from camera traps can be used to describe the patterns and monitor the occupancy, abundance, and richness of wildlife, essential information for conservation in times of rapid climate and land‐cover changes. Habitat loss and poaching are responsible for historical population losses of mammals in the Atlantic Forest biodiversity hotspot, especially for medium to large‐sized species. Here we present a data set from camera trap surveys of medium to large‐sized native mammals (>1 kg) across the Atlantic Forest. We compiled data from 5380 ground‐level camera trap deployments in 3046 locations, from 2004 to 2020, resulting in 43,068 records of 58 species. These data add to existing data sets of mammals in the Atlantic Forest by including dates of camera operation needed for analyses dealing with imperfect detection. We also included, when available, information on important predictors of detection, namely the camera brand and model, use of bait, and obstruction of camera viewshed that can be measured from example pictures at each camera location. Besides its application in studies on the patterns and mechanisms behind occupancy, relative abundance, richness, and detection, the data set presented here can be used to study species' daily activity patterns, activity levels, and spatiotemporal interactions between species. Moreover, data can be used combined with other data sources in the multiple and expanding uses of integrated population modeling. An R script is available to view summaries of the data set. We expect that this data set will be used to advance the knowledge of mammal assemblages and to inform evidence‐based solutions for the conservation of the Atlantic Forest. The data are not copyright restricted; please cite this paper when using the data.

Achieving conservation outcomes in plant mitigation translocations: the need for global standards - Chantelle A. T. Doyle; Thomas Abeli; Matthew A. Albrecht; Joe Bellis; Bruno Colas; Sarah E. Dalrymple; Andreas Ensslin; Jaime Espejo; Paul L. A. Erftemeijer; Margaux Julien; Wolfgang Lewandrowski; Hong Liu; et al. (Plant Ecology, 2023)
Many countries have legislation intended to limit or offset the impact of anthropogenic disturbance and development on threatened plants. Translocations are often integral to those mitigation policies. When translocation is used exclusively to mitigate development impacts, it is often termed a ‘mitigation translocation.’ However, both the terminology and processes vary regarding interpretation and application, resulting in inconsistent standards, often leading to poorly planned and implemented projects. These mitigation projects rarely achieve the intended ‘no net loss’ of protected species due to issues with timelines and procedures that result in the mortality of translocated individuals. Instead, such projects are often process driven, focused on meeting legislative requirements which enable the development to proceed, rather than meaningful attempts to minimise the ecological impact of developments and demonstrate conservation outcomes. Here, we propose to reframe mitigation translocations as conservation driven, ensuring best practice implementation and hence, a quantified no net loss for impacted species. These methods include redefining the term mitigation translocation to include conservation objectives and outlining issues associated with the mitigation translocation processes worldwide. We also nominate global standards of practice to which all proposals should adhere, to ensure each project follows a trajectory towards quantified success, with genuine impact mitigation. These proposed standards focus on building efficient translocation plans and improving governance to facilitate a transition from project centred to ecology-driven translocation. Employment of these standards is relevant to development proponents, government regulators, researchers, and translocation practitioners and will increase the likelihood of conservation gains within the mitigation translocation sector.

Monitoring time of conservation-driven and mitigation-driven plant translocations in Europe - Margaux Julien; Bertrand Schatz; Alexandre Robert; Bruno Colas (Plant Ecology, 2023)

The relevance of plant translocation as a conservation tool in France - Mohamed Diallo; Anaël Mayeur; Anne-Charlotte Vaissière; Bruno Colas (Plant Ecology, 2023)

Combining expert knowledge and models in participatory workshops with farmers to design sustainable weed management strategies - Wilfried Queyrel; Bastien Van Inghelandt; Floriane Colas; Nicolas Cavan; Sylvie Granger; Bérénice Guyot; Raymond Reau; Damien Derrouch; Bruno Chauvel; Thibault Maillot; Nathalie Colbach (Agricultural Systems, 2023)

Differential effects of major inhibitory compounds from sugarcane-based lignocellulosic hydrolysates on the physiology of yeast strains and lactic acid bacteria - Priscila Cola; Dielle Pierotti Procópio; Adriana Tabosa de Castro Alves; Luciana Rebelo Carnevalli; Icaro Viana Sampaio; Bruno Labate Vale da Costa; Thiago Olitta Basso (Biotechnology Letters, 2020)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Floral morphology as the main driver of flower-feeding insect occurrences in the Paris region - James Desaegher; Sophie Nadot; Colin Fontaine; Bruno Colas (Urban Ecosystems, 2018)

Buzz in Paris: flower production and plant–pollinator interactions in plants from contrasted urban and rural origins - James Desaegher; Sophie Nadot; Isabelle Dajoz; Bruno Colas (Genetica, 2017)

French experts report on MUTYH-associated polyposis (MAP) - Bruno Buecher; Catherine Bonaïti; Marie-Pierre Buisine; Chrystelle Colas; Jean-Christophe Saurin (Familial Cancer, 2012)

Variation in Dispersal Traits in a Narrow-endemic Plant Species, Centaurea corymbosa Pourret. (Asteraceae) - Miquel Riba; Agnés Mignot; Héléne Fréville; Bruno Colas; Eric Imbert; Denis Vile; Myriam Virevaire; Isabelle Olivieri (Evolutionary Ecology, 2005)

Role of Corridors in Plant Dispersal: an Example with the Endangered Ranunculus nodif lorus - Florian Kirchner; Jean‐Baptiste Ferdy; Christophe Andalo; Bruno Colas; Jacques Moret (Conservation Biology, 2003)
The proposition that the migration of organisms between habitat patches could be enhanced by corridors has been much discussed among conservation biologists. But the few experimental studies supporting the usefulness of corridors have all concerned animal species. We investigated the role of corridors in seed dispersal, studying population genetic and demographic structure in metapopulations of the rare, pond‐dwelling, autogamous plant species Ranunculus nodiflorus L. in the Fontainebleau Forest ( France ). Differentiation on three polymorphic isozyme markers was strong among local populations ( ponds ) within metapopulations ( sites ) and moderate among metapopulations. Partial Mantel tests revealed that the connection of ponds through temporarily flooded natural corridors, facilitating seed migration, had a strong negative effect on genetic differentiation between local populations and that a pond was more likely to be colonized when connected by corridors to other occupied ponds. Thus, corridors are probably a key element of landscape structure for metapopulation dynamics in R. nodiflorus. From a conservation perspective, our results suggest that corridors could increase the chance of persistence of plant species living in fragmented habitats by promoting seed dispersal between habitat patches.

Population structure of an endangered species living in contrasted habitats: Parnassia palustris (Saxifragaceae) - Isabelle Bonnin; Bruno Colas; Cécile Bacles; Anne‐Catherine Holl; Frédéric Hendoux; Benoit Destiné; Frédérique Viard (Molecular Ecology, 2002)
In endangered species, it is critical to analyse the level at which populations interact (i.e. dispersal) as well as the levels of inbreeding and local adaptation to set up conservation policies. These parameters were investigated in the endangered species Parnassia palustris living in contrasted habitats. We analysed population structure in 14 populations of northern France for isozymes, cpDNA markers and phenotypic traits related to fitness. Within population genetic diversity and inbreeding coefficients were not correlated to population size. Populations seem not to have undergone severe recent bottleneck. Conversely to pollen migration, seed migration seems limited at a regional scale, which could prevent colonization of new sites even if suitable habitats appear. Finally, the habitat type affects neither within‐population genetic diversity nor genetic and phenotypic differentiation among populations. Thus, even if unnoticed local adaptation to habitats exists, it does not influence gene flow between populations.

Fire and species range in Mediterranean landscapes: an experimental comparison of seed and seedling performance among Centaurea taxa - Miquel Riba; Anselm Rodrigo; Bruno Colas; Javier Retana (Journal of Biogeography, 2002)
Aim Fire is a major disturbance event in Mediterranean landscapes. In this paper, we experimentally assess the effects of fire and post‐fire conditions on seed germination and establishment of twenty Centaurea taxa to test whether differences among taxa are associated with range size. Methods The taxa (species and subspecies) considered were classified as rare and widespread according to their `area of occupancy' in the Mediterranean coast of Spain and France. In a first experiment, we analyse the effects of heat‐shock (particularly, room temperature, 70 and 110 °C) on percentage germination and speed of germination (T50). In a second experiment, we analyse the effects of post‐fire conditions (shading and soil type: burned/unburned) on seed germination and establishment ability. Results Temperatures over 120 °C resulted in 100% mortality, while temperatures in the range of those expected to be found in the first centimetres down the soil profile during a wildfire (70–110 °C) had no effect on seed germination. Differences in germination percentage and T50 among taxa were not related to rarity. In the post‐fire conditions experiment, decreased radiation (shading) increased percentage germination and T50 in most taxa, while burned soil decreased germination in some of them. The effects of post‐fire conditions on seedling growth (number of leaves and leaf size) were also different among taxa, but such differences were not related to rarity. However, rarity was associated with low establishment ability, as rare taxa tended to show smaller seedling size and higher mortality rates under the whole range of conditions tested. Main conclusions The results obtained indicate that fire has a negative effect upon the survival of populations in all the taxa considered, and that rare‐common differences in germination and seedling establishment are not directly related to disturbance by fire. As far as interspecific differences in range size are concerned, other factors, either alone or in combination with a low regeneration ability after fire, need to be explored further.

Predicting Endemism from Population Structure of a Widespread Species: Case Study in Centaurea maculosa Lam. (Asteraceae) - Helene Freville; Bruno Colas; Joelle Ronfort; Miquel Riba; Isabelle Olivieri (Conservation Biology, 1998)

Predicting Endemism from Population Structure of a Widespread Species: Case Study in Centaurea maculosa Lam. (Asteraceae) - Hélène Fréville; Bruno Colas; Joëlle Ronfort; Miquel Riba; Isabelle Olivieri (Conservation Biology, 1998)
Amounts of genetic variability, genetic differentiation among taxa and populations, and population sizes were studied in five populations of Centaurea maculosa ssp. maculosa (a widespread taxon), all six populations of C. corymbosa (a narrowly endemic species), and the single population of C. maculosa ssp. albida . Seventeen isozyme loci were studied, of which nine were polymorphic. Results suggest that C. corymbosa and C. maculosa ssp. albida are likely derived from C. maculosa ssp. maculosa because the former represent a sample of the diversity of the latter. The percentage of polymorphic loci and Nei’s genetic diversity were positively and significantly correlated with population size over all populations, but not within each taxon. Populations of both the widespread C. maculosa ssp. maculosa and the rare C. corymbosa were strongly differentiated: overall, F ST values were 0.26 and 0.34, respectively. Differentiation among populations of different taxa was of the same order of magnitude as that observed among populations within taxa. Nevertheless, significant differentiation among the three taxa was found by a hierarchical analysis of variance on allele frequencies. We suggest that bottlenecks or founder effects associated with colonization events and ecological specialization in some populations of C. maculosa ssp. maculosa have led to new taxa such as C. corymbosa and C. maculosa ssp. albida . This may be a direct consequence of the particularly strong differentiation among populations of the widespread C. maculosa ssp. maculosa . Our study highlights the utility of considering closely related widespread taxa in order to understand the population biology and evolution of rare species, as well as to design proper management programs. Predicciones de Endemismo a Partir de la Estructura Poblacional de una Especie con Amplia Distribución: Estudio del Caso de Centaurea maculosa Lam. (Asteraceae) So determinó la variabilidad genética, la diferenciación genética entre taxones y entre poblaciones, y el tamaño de población en 5 poblaciones de Centaurea maculosa ssp. maculosa (un taxón de amplia distribución), las 6 únicas poblaciones de C. corymbosa (especie endémica), y la única población de C. maculosa ssp. albida existente. Se estudiaron diecisiete loci enzimáticos, de los cuales 9 fueron polimórficos. Los resultados sugieren que los dos taxones endémicos probablemente derivaron del taxón de amplia distribución, ya que los primeros representan una muestra de la diversidad de este último. Tanto el porcentaje de loci polimórficos como la diversidad genética (índice de Nei) mostraron una correlación positiva con el tamaño de la población. Se encontró una fuerte diferenciación entre las poblaciones tanto en el taxón endémico como en el de amplia distribución: los valores de F ST globales fueron 0.34 para C. corymbosa y 0.26 para C. maculosa ssp. maculosa. La diferenciación entre poblaciones de taxones diferentes fue del mismo orden de magnitud que la observada entre poblaciones dentro de un mismo taxón. Sin embargo, un análisis de la varianza jerárquico de las frecuencias génicas reveló una diferenciación significativa entre los tres taxones. Se sugiere que la aparición de taxones endémicos como C. corymbosa y C. maculosa ssp. albida se debe a efectos fundacionales, como consecuencia de “cuellos de botella” o procesos de colonización, y posterior especialización ecológica en algunas poblaciones de C. maculosa ssp. maculosa . Esto sería una consecuencia directa de la fuerte diferenciación entre poblaciones de C. maculosa ssp. maculosa . Este estudio remarca la utilidad del uso de especies de amplia distribución estrechamente emparentadas con especies endémicas para comprender la biología y evolución de especies raras, así como para diseñar programas de manejo adecuados.